Foresight as a way of predicting the future digital face of science - M. Yu. Zakharov; A. V. Shishkova (Вестник университета, 2025)
The article is devoted to the analysis of some current problems caused by digital transformation of modern science, in particular, the possibility of using foresight technology to understand its future and development paths. The science has begun to perform its prognostic function based on cognitive tools, clothed in the form of scientific methodology, and with the help of a special scientific language, having initially given the resulting knowledge a probabilistic nature. Positive consequences of digitalisation of the science are analysed, risks and threats faced by the modern science are named. It is proven that problems of security of digital knowledge and digital information are coming to the fore. Significant experience in using the foresight for prognostic purposes of scientific activity is studied, and the meaning of the foresight as an impact on the future of the science in order to build its desired future is revealed. Strengths and various (technological, algorithmic, socio-cultural, ontological, and ethical) limitations of the foresight methodology are identified, and ways to resolve them are outlined. A philosophical approach to study of the digital transformation of the science is presented. It is shown that it should serve not only as a tool for analysing current changes, but also as a basis for the formation of future scientific knowledge, for the development of new approaches to the scientific knowledge in the digital age.